Empowering Educators in Gayo Lues through Digital Literacy and Virtual Tour Technology - Riyani, Mufti; Aprilia, Rapita; Rahman, Aulia; Anis, Madhan (Universitas Lambung Mangkurat, 2025)
This community service program aims to empower educators in Gayo Lues through improving digital literacy and utilizing local culture-based virtual tour technology. This program replicates the Langsa Multicultural Heritage Virtual Tour, an innovative learning tool previously developed through a research program. Based on the mapping of current conditions, the primary target group was 18 teachers from the Sekulen Private Elementary School. The educators were accompanied by 30 students from the Period II Community Service Program at Samudra University, who served as mentors. The method applied was a Participatory Action Research (PAR) Framework combined with Asset-Based Community Development (ABCD). This method involved participatory mapping to assess current conditions, collaborative workshops, co-creation of digital content, and classroom mentoring for implementation. As a result, technical skills, such as producing 360° photos as a basic element of virtual tours and developing them in Google Sites, can be mastered by teachers with the available resources. In addition, there was a significant increase in teachers' digital literacy scores from an average of 45.0 to 78.2 or 74%. The program's outputs include the Gayo Lues Heritage Virtual Tour platform, digital lesson plan modules, and improved teacher capacity for technology integration in learning. This activity has provided digital-based teaching materials that can be used in the classroom as well as the potential to help other sectors such as tourism and cultural heritage preservation.